Peran Strategis Pelayanan Puskesmas Cieurih dalam Meningkatkan Kesadaran Masyarakat Terhadap Pola Hidup Sehat di Kecamatan Cipaku - Meli Melinda; Dini Yuliani; Neti Sunarti (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the strategic role of the Cieurih Community Health Center in increasing public awareness of healthy lifestyles, particularly in the Cipaku Sub-district. Employing a qualitative descriptive approach, data were collected through observation, in-depth interviews with key stakeholders, and documentation of program activities. The collected data were analyzed using three stages: data reduction, data presentation, and drawing conclusions with verification to ensure validity. The analysis focuses on three main dimensions of the Health Center’s role: (1) Interpersonal Role, which involves direct interaction with the community to build trust, encourage participation, and foster behavioral change; (2) Informational Role, which encompasses the dissemination of accurate health information, educational campaigns, and correction of misinformation; and (3) Decisional Role, which relates to planning, implementing, and evaluating health programs in response to local needs.The findings reveal that the Cieurih Community Health Center has made significant contributions to raising awareness and promoting healthy living practices through these roles. Initiatives such as health counseling, mobile clinic services, and collaborative activities with community leaders have shown positive influence. However, the study also identifies persistent challenges, including low levels of community participation, insufficient financial and human resources, and the strong influence of traditional cultural practices and misinformation that hinder optimal outcomes. To address these obstacles, adaptive strategies are necessary. Recommendations include the development of personalized approaches tailored to the socio-cultural context, the use of innovative communication methods such as social media and visual storytelling, and the strengthening of cross-sectoral collaboration with educational institutions, religious leaders, and local government agencies. These measures are expected to enhance community engagement, improve the accuracy and reach of health information, and sustain the long-term impact of health promotion programs.